Enhancement of Growth Parameters and Productivity of Basmati Rice through Summer Green Manuring and Zinc Fertilization - Singh, Amarpreet; Singh Shivay, Yashbir (International Journal of Bio-resource and Stress Management, 2023)
Field experiments were conducted during summer and rainy (kharif) seasons (April- November) of 2009 and 2010 for two consecutive years at the research farm of the Indian Agricultural Research Institute, New Delhi, to evaluate the effects of summer green manuring crops and zinc (Zn) fertilizer sources on growth and physiological development of Basmati rice (Oryza sativa L.). Summer green manure residue incorporation and zinc fertilization significantly enhanced the growth and physiological development of Basmati rice. Incorporation of Sesbania aculeata (Dhaincha) led to a significant increase in growth parameters, yield attributes and grain and straw yields of succeeding Basmati rice. EDTA-chelated Zn (12% Zn) application significantly improved the growth parameters, yield attributes and grain and straw yields of succeeding Basmati rice over other zinc sources as well as control (no zinc application). Sesbania aculeata (Dhaincha) residue incorporation and EDTA-chelated Zn (12% Zn) treatments were found to be a better combination with respect to Basmati rice growth and physiological development. The correlation among the various yield attributes and yield indicated that all the yield attributes were highly correlated with yield. Thus, adequate Zn fertilization along with green manure incorporation can lead to better growth and physiological development for higher productivity of Basmati rice.